Examining change management theories through case studies (International Journal of Scientific Research and Management (IJSRM), 2021)
The objective of the present paper is to examine the already established change management success factors and respective theories, in the light of personal experience in five organizations as a change agent. And examine whether these theories are sufficient to explain the success and failure of change management in Indian organisations. We took the constructivists approach while studying the change management phenomenon. Hence, we relied on a qualitative method. As there is no single truth, the reality needs to be interpreted and the truth discovered based on the collective experiences of the researchers. Therefore, the theoretical perspective of our research is interpretivism. We have used narrative inquiry based on memory as we have first-hand knowledge over a period in each of the five cases and in some cases; we both have experience in a different time period. This approach is appropriate in this case of knowledge of change management, which is unquantifiable and where it is not easy to transfer the experience. Our findings mostly support the existing theories and steps in change management. Out of the ten steps one step is ““Form partnership with stakeholders for guiding coalition” is not supported. Existence of good management practices are a perquisite for a successful change. Institutionalize change is an important step. As there is a gap between observation and articulation of this paper there are chances of missing important observations that could have considered for drawing more insightful conclusion. The study is based on individual’s observation therefore it may have cognitive biases. The case study narratives will give an insight to a practitioner how different organisations management change management process. The findings presented will also be helpful to a practitioner. The strongest new finding is the need to have the good management practices in place before going ahead with change.